The involvement of male homosexuals with mainstream newspapers’ reporting of homosexuality / Mohd Shahnawi Muhmad Pirus - Muhmad Pirus, Mohd Shahnawi (Institute of Graduate Studies, UiTM, 2017)
The contributory factors to male homosexuals’ (MH) involvement with mainstream newspapers reporting of homosexuality was observed on news content representation including the reporting criterion and its consistency to be reported to the audiences, triggering the public interest in receiving information and advocating themselves towards a guided living culture. This study was guided with two theories; (i) Uses and Gratifications Theory, and (ii) Social Judgment Theory following a series of content analysis on newspapers reporting of homosexuality that was conducted to understand how it was presented. Using a qualitative approach with phenomenology and popular culture paradigms, informants of male homosexuals from the non-governmental organization were selected randomly through the purposive and judgmental sampling strategies…